The Leadership Qualities of Midwives When Collaborating With Nurses During Postpartum - Palimbo, Adriana; Sari, Anggrita; Mahdiyah, Dede; Sogi S. Redjeki, Dwi (KnE Social Sciences, 2023)
Leadership and collaboration aid in communicating, coordinating, and negotiating to achieve common goals. This study aimed to analyze the leadership qualities of midwives when collaborating with nurses in postpartum services in community health centers. This was a descriptive-analytic study with a cross-sectional design. The research subjects were 30 midwives in charge of maternal health for 42 days postpartum. Data were collected through a questionnaire that included four leadership indicators: directive, consultative, participatory, and delegating. Postpartum service coverage was measured by the frequency of postpartum maternal visits and included KIE and health promotion. The results showed a significant correlation between collaborative leadership and postpartum service coverage in the directive function (p=0.002), the consultative function (p=0.042), the participatory function (p=0.000), and the delegation function (p=0.028). The most significant correlation was the participatory function with an OR value of 8.011 (95% CI = Lower 1.315 - Upper 21.052). Practical implications in the future require strengthening organizational culture factors and empowering the community to access services and utilize available health information. Keywords: Leadership Effect, Collaboration, Postpartum Service Coverage